Population Issues in the 21st Century : The Role of the World Bank - World Bank (World Bank, Washington, DC, 2013)
The objective of this paper is to discuss some obstacles and opportunities presented by population processes in order to prioritize areas for investment and analytical work as background information for the 2007 HNP Sector Strategy. Within HNP, two areas fall within population: (1) reproductive, maternal, and sexual health issues, and the health services that address them; and (2) levels and trends in births, deaths, and migration that determine population growth and age structure. Many of the aspects of delivery of sexual and reproductive health services are addressed in the overall sector strategy. This paper, therefore, focuses on the determinants and consequences of demographic change, and on policies and interventions that pertain to fertility and family planning. The paper consists of five sections. First, this section defines the scope of population as used in the HNP sector, and the areas that will be considered in this note are specified. This is followed by a description of recent trends in demographic indicators that have created the demographic backdrops for addressing development issues. The third section discusses the role the World Bank can play in population issues and places population within the context of economic growth, poverty reduction, and equity considerations. The fourth section deals with the global policy context since the 1994 Cairo International Conference on Population and Development (ICPD) which has guided the priorities of developing countries and donors in the past 13 years. The final section discusses collaboration between World Bank and partner development agencies in addressing different aspects of population.